An expanded access program of risdiplam for patients with Type 1 or 2 spinal muscular atrophy. Issue 6 (14th May 2022) - Kwon, Jennifer M.; Arya, Kapil; Kuntz, Nancy; Phan, Han C.; Sieburg, Cory; Swoboda, Kathryn J.; Veerapandiyan, Aravindhan; Assman, Beverly; Bader‐Weder, Silvia; Dickendesher, Travis L.; Hansen, Jennifer; Lin, Helen; et al.
Abstract: Objective: The US risdiplam expanded access program (EAP; NCT04256265) was opened to provide individuals with Type 1 or 2 spinal muscular atrophy (SMA) who had no satisfactory treatment options access to risdiplam prior to commercial availability. The program was designed to collect safety data during risdiplam treatment. Methods: Patients were enrolled from 23 non‐preselected sites across 17 states and treated with risdiplam orally once daily. Eligible patients had a 5q autosomal recessive Type 1 or 2 SMA diagnosis, were aged ≥2 months at enrollment, and were ineligible for available and approved SMA treatments or could not continue treatment due to a medical condition, lack/loss of efficacy, or the COVID‐19 pandemic. Results: Overall, 155 patients with Type 1 ( n = 73; 47.1%) or 2 SMA ( n = 82; 52.9%) were enrolled and 149 patients (96.1%) completed the EAP (defined as obtaining access to commercial risdiplam, if desired). The median treatment duration was 4.8 months (range, 0.3–9.2 months). The median patient age was 11 years (range, 0–50 years), and most patients ( n = 121; 78%) were previously treated with a disease‐modifying therapy. The most frequently reported adverse events were diarrhea ( n = 10; 6.5%), pyrexia ( n = 7; 4.5%), and upper respiratory tract infection ( n = 5; 3.2%). The most frequently reported serious adverse event was pneumonia ( n = 3; 1.9%). No deaths were reported. Interpretation: In the EAP, the safety profile of risdiplam was similar to what was reported in pivotal risdiplam clinical trials. These safety data provide further support for the use of risdiplam in the treatment of adult and pediatric patients with SMA.